A matter of timing: The religious factor and morality policies. Issue 1 (16th June 2017) - Budde, Emma T.; Knill, Christoph; Fernández‐i‐Marín, Xavier; Preidel, Caroline
Abstract : The question of whether or not religion accounts for variance in the governance of moral issues, between and within countries over time, has long been debated but never conclusively answered. A novel data set encompassing innovative measurements of state regulation of "life‐and‐death" issues and of the religious stratification of society enables us to answer why previous studies reached contradictory results. The time‐series cross‐sectional analysis of 26 countries over 50 years reveals that dominant religious denominations in society indeed influence state governance approaches regarding the issues of abortion and euthanasia. This denominational effect is shown to be contingent on the religiosity of a country's population, but independent from the formal state–church relationship. Lastly, it is shown that the religious effect has an inverse U‐shaped relationship with time, exposing the timeframe of analysis as decisive for inferences drawn in the study of morality policy.